Impacts of the COVID-19 pandemic on the health of university teachers and students: a scoping review - Guimarães de Araujo Faria, Magda; da Silva Freitas Venâncio, Christiane Gleyce; Carvalho Pacheco, Fádia; Ferreira Koopmans, Fabiana; Valadão Vasconcelos Alves, Luciana; Maia Valente, Patrícia (Frontiers in Psychology, 2025)
ObjectiveTo identify the impacts of the COVID-19 pandemic on the health of university professors and students. Method: Scoping review following the protocol recommended by the Joanna Briggs Institute. The research question followed the order imposed by the mnemonic “PCC” (Population, Concept, and Context), namely: what are the impacts of the COVID-19 pandemic on the health of university professors and students?ResultsThe analysis sample consisted of 29 texts in article format. Two main categories of health repercussions were observed, namely: category 1—repercussions on mental health; category 2—repercussions on physical health.ConclusionIt is understood that harmful effects on mental health will be an ever-present reality in the university context, since exhaustion is a characteristic of academic work itself. This situation can have serious consequences for the individual, requiring intervention projects combined with public policies that minimize these effects. It is necessary to review the role of the university in today’s society.